Genótipos de capim-elefante para produção de energia na forma de combustão - Favare, Henrique Guimarães de (2019)
The objective was to evaluate the agronomic characteristics, the chemical composition of elephant grass genotypes (Pennisetum purpureum Schum.) For energy production in the form of combustion. The experiment was conducted in the Experimental field of the company Mato-grossense of Research, Assistance and Rural Extension (EMPAER) in Cáceres-MT. The experimental design was a randomized block with three replicates. The treatments were arranged in a split plots scheme, considering as genotype plot and cuttings (dry and water) as subplots. The thirteen genotypes evaluated were Cubano Pinda, Porto Rico, Vruckwona, Piracicaba 241, Cuba 116, Taiwan A-25, Mercker, Napier, Canará, Guaçu, Cameroon and the clones CNPGL 93-41-1 and CNPGL 91-25-1. The experimental unit consisted of four rows of 5.0 m in length with spacing between rows of 1.0 m, totaling 20 m2 . The experiment lasted two consecutive years, with a cut made every six months counting from the standardization cut (March/2016), with a cut in the drought (September) and one in the waters (March), totaling four cuts. The agronomic characteristics (plant height, leaf blade length and width, stem diameter, number of tillers, dry matter yield and stem percentage) were evaluated; bromatological composition (dry matter, neutral and acid detergent fiber, hemicellulose, volatile matter and fixed carbon); mineral composition (concentrations of phosphorus, potassium, calcium, magnesium, sulfur and nitrogen). The genotypes with the highest yields of dry matter, plant height and stem diameter were CNPGL 91-25-1, Cubano Pinda, BRS Canará, Porto Rico and Mercker. Larger levels of dry matter, acid detergent fiber and volatile matter occur in the dry period of the year and in the following genotypes Mercker, Piracicaba 241, Guaçu, Cubano Pinda and BRS Canará. Smaller concentrations of phosphorus (water), potassium (dry) and magnesium (dry and water) are found in the genotypes Cuba 116, Piracicaba 241, Vruckwona, Porto Rico, BRS Canará and Cubano Pinda. Analyzing the agronomic characteristics, bromatological and mineral composition, the elephantgrass genotypes recommended for the production of energy in the form of combustion are BRS Canará and Cubano Pinda.